The 9th International Conference "Environmental Engineering 2014" 2014
DOI: 10.3846/enviro.2014.038
|View full text |Cite
|
Sign up to set email alerts
|

Impact of closed Kairiai landfill on the Ginkūnai Pond, Lithuania

Abstract: The main goal of this study was to investigate the impact of the closed Kairiai municipal landfill located near Šiauliai City on the Ginkūnai Pond, into which the leachate from the landfill is released. The main aim of our study was to determine the phytotoxic impact of landfill leachate, water and bottom sediments of the Ginkūnai Pond and Švedė Creek, as well as drainage channel through which the leachate is discharged into the pond. The main characteristics of physico-chemical analysis of the leachate, water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
2
0
1
Order By: Relevance
“…The landfills could remain a permanent pollution sources for long periods of time after closing (Pablos et al 2011;Klauck et al 2013). For example, physico-chemical investigation, phytotoxicity testing and use of battery of biotests (leech, crustacean and fish) showed that the Kairiai landfill closed in 2007 remains a serious source of long-lasting pollution, which adversely affects the neighboring water bodies (Svecevičius et al 2013;Montvydienė et al 2014). Such problems can be potentially even worse when leachates are percolating into trans-boundary Rivers (i.e.…”
Section: Problems Of Environmental Inventory Of Old Small Landfillsmentioning
confidence: 99%
See 1 more Smart Citation
“…The landfills could remain a permanent pollution sources for long periods of time after closing (Pablos et al 2011;Klauck et al 2013). For example, physico-chemical investigation, phytotoxicity testing and use of battery of biotests (leech, crustacean and fish) showed that the Kairiai landfill closed in 2007 remains a serious source of long-lasting pollution, which adversely affects the neighboring water bodies (Svecevičius et al 2013;Montvydienė et al 2014). Such problems can be potentially even worse when leachates are percolating into trans-boundary Rivers (i.e.…”
Section: Problems Of Environmental Inventory Of Old Small Landfillsmentioning
confidence: 99%
“…Ecotoxicological reseach of toxicants, WW and ll in lithuania. Ecotoxicity investigations of various individual toxicants or their mixtures, WW, LLs were undertaken with standard aquatic organisms of different phylogenetic levels (bacterium, crustacean, algae, fish (četkauskaitė, Bražėnaitė 2004;Kalcienė, četkauskaitė 2007); and ontogenetic stages (fish embryos, larvae, adults) (Kazlauskienė, Vosylienė 2008;Svecevičius 2006;Vosylienė et al 2010;Svecevičius, Kazlauskienė 2011;Montvydienė et al 2014). Chemical analysis and biotest battery data based ecotoxicological evaluations of municipal WW from regional WW treatment plants of Lithuania cities were implemented in 2007 and 2010 (Manusadžianas et al 2010;COHIBA 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Kairių sąvartyno filtrate nustatyti sunkieji metalai: Cu, Zn, Ni, Cr, Pb, Hg, Cd, Mn, Co (Montvydienė et al 2014;Vasarevičius et al 2005).…”
Section: įVadasunclassified